Correlation of biochemical and histopathological findings in acute viral hepatitis - Valdivia Carpio, Héctor (1967)
The presence and extent of liver injury and the subsequent degree of functionality, can be assessed with relative safety for a variety of biochemical methods. These correlative studies have been carried out for years (1-6) and the results have been consistent in the sense that adequate testing and association with some other very significant there. It is the purpose of this paper try to establish which functional tests better reflect the degree of liver damage and, therefore, diagnosis and evolutionary rate of the disease in an environment like ours, where liver biopsy is often difficult to carry it out particularly serially.